IMMOBILIZATION OF ZINC OXIDE NANOPARTICLES IN CHITOSAN-GELATIN COMPOSITE MEMBRANE FOR ANTIBACTERIAL ACTIVITY - J. V. MESHRAM,; S. H. PAWAR, (International Journal of Pharma and Bio Sciences, 2015)
Novel chitosan-gelatin/Zinc Oxide nanoparticles (C-G/ZnO NPs) composites with enhanced anti bacterial activity is prepared by casting method at room temperature. In the present work, the combination of chitosan gelatin with ZnO for antibacterial activity is reported. Antibacterial activity of each nanocomposite is observed for Gram negative E. coli and Gram positive S. aureus. Prepared samples were characterized by XRD to study the morphology and to determine the crystallite size of ZnO NPs. The crystallite size is calculated to be 27nm by Debye-Scherrer formula. The UV-Vis spectroscopy was used to study the absorbance patterns of ZnO NPs in composite membranes. UTM was used to calculate the tensile strength and % elongation. The results showed the excellent strength value of 93.8 MPa for 1% ZnO NPs compositions. The tensile strength and antibacterial activity studies showed the potential of the nanocomposites to be used in biomedical applications.